Mitral annular calcification in hypertrophic cardiomyopathy. (15th February 2022) - Massera, Daniele; Xia, Yuhe; Li, Boyangzi; Riedy, Katherine; Swistel, Daniel G.; Sherrid, Mark V.
Abstract: Background: Changes in mitral valve anatomy contribute to left ventricular outflow tract obstruction (LVOTO) in hypertrophic cardiomyopathy (HCM). Mitral annular calcification (MAC) is common among patients with HCM but its implications are currently unknown. Methods: We tested the hypothesis that echocardiographic MAC would be associated with anterior displacement of the mitral valve and LVOTO in a cohort of 304 patients with HCM aged ≥ 60 years (mean [SD] age 71.6 [7.7] years, 52% women). Results: MAC was present in 141 (46%) patients. The mean (SD) MAC offset distance was 9.8 (4.8) mm. A higher proportion of those with MAC compared to those without MAC had SAM (84.2 vs. 63.8%, p  < 0.001) and LVOTO (80.9 vs. 57.9%, p  < 0.001). In patients with MAC, the septal-mitral valve distance was shorter compared to those without (19.4 [4.0] vs 21.5 [4.9] mm, p  < 0.001). The mitral valve position ratio was greater in those with MAC compared to those without (1.00 [0.79, 1.22] vs. 0.86 [0.67, 1.05], p  < 0.001) denoting greater anterior displacement, especially in those with MAC and LVOTO. After multivariable adjustment, MAC offset distance was associated with LVOTO (OR 1.16 [95% CI 1.07, 1.28] per mm, p  = 0.001). Over a median follow-up of 2.7 years, 42 (29.8%) patients with MAC underwent surgery to relieve LVOTO, with no deaths. Conclusion: This study adds MAC to the known geometrical alterations of the mitral valve that predispose to LVOTO and suggests that surgical relief of LVOTO in the presence of MAC is safe when performed by an experienced surgeon. Highlights: MAC is common among patients with HCM ≥ 60 years. MAC is associated with anterior displacement of mitral coaptation. MAC contributes to the pathophysiology of LVOT obstruction. HCM surgery in the presence of MAC is safe when performed by an experienced surgeon.